Diseño de un prototipo de invernadero automatizado e implementación de estrategias de control PID y On-Off para el control de temperatura y humedad, supervisadas por medio de la plataforma ThingSpeak y almacenamiento de datos en MySQL (2020)
The first industrial greenhouses were unveiled in the mid-16th century in the Netherlands in order to preserve grape crops, where the heating generated, and the necessary amount of sunlight made the plants grow rapidly. For this reason agriculture, which has always been developed by land crops and human labor, has been developing a progressive transformation where now, with the help of science, many more processes in technology and innovation are carried out to introduce them to agriculture. with the sole purpose of obtaining better quality products at lower costs and reduced space. On the other hand, the current technological revolution involves the digitization of industrial processes and systems with the integration of different disciplines such as automatic control, efficient consumption of energy, communication and industrial instrumentation with the sole purpose of optimizing resources, saving time and service customization. With this, the digital transformation brings relevant and characteristic changes in each of the sectors where it has been applied, where agriculture and technology accommodate what is called agrotechnology, which is all the technological innovation implemented in agriculture. And it has great involvement in recent times due to the integration of all the technologies that have been developed to execute them in all agricultural practices. For this reason, agriculture is not exempt from the effect of the technological revolution, where more and more new studies allow a total turn to be made to this primary sector in each country and generate a positive impact on society and the economy. Thanks to technological advances, technology in agriculture will continue to grow with the use of different types of automation, variable control, specialized tool, among others, that will make agriculture generate a healthy interaction with the environment and achieve better results. of agricultural productivity and sustainability.